2022
DOI: 10.22219/sinjie.v1i1.20992
|View full text |Cite
|
Sign up to set email alerts
|

Al-Qur'an Literacy Model in Indonesian Islamic Universities (Case Study at IAIN Kediri, East Java)

Abstract: This modern research aims to understand the model of al-Qur'an literacy in Islamic universities in Indonesia. This research uses constructivism paradigm with descriptive qualitative approach and case study research type. Research informants consisted of the person in charge of the Qur'an literacy program, managers, tutors, and students. Data were collected using field observations, interviews and documentary techniques, while data analysis was carried out using an interactive model through data condensation, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(23 reference statements)
0
2
0
1
Order By: Relevance
“…Karena anak harus bisa membedakan pengucapan, huruf, dan penulisan setiap huruf hijaiyah, pembelajaran huruf hijaiyah cenderung mengacu pada bahasa bagian pendengaran. Bunyi, bentuk huruf, dan penulisan setiap huruf hijaiyah adalah unik sehingga untuk mempelajarinya pun juga membutuhkan teknik tertentu (Khotimah et al, 2022). Hasil temuan tersebut dapat didiskusikan dengan teori yang menyatakan bahwa komponen penting dalam pengembangan membaca dan menulis adalah pengenalan huruf.…”
Section: Fitur Makharijul Hurufunclassified
“…Karena anak harus bisa membedakan pengucapan, huruf, dan penulisan setiap huruf hijaiyah, pembelajaran huruf hijaiyah cenderung mengacu pada bahasa bagian pendengaran. Bunyi, bentuk huruf, dan penulisan setiap huruf hijaiyah adalah unik sehingga untuk mempelajarinya pun juga membutuhkan teknik tertentu (Khotimah et al, 2022). Hasil temuan tersebut dapat didiskusikan dengan teori yang menyatakan bahwa komponen penting dalam pengembangan membaca dan menulis adalah pengenalan huruf.…”
Section: Fitur Makharijul Hurufunclassified
“…The Tashih Recitation Program actually has a significant effect on increasing the ability to read the Qur'an in accordance with the rules of tajwid science. (Khotimah et al, 2022;Morrissey, 2021) who found that mastery of Tashih Recitations will have a significant effect on learning outcomes of the Qur'an. This is also supported by Fauji et al, (2020); Munawaroh et al, (2022); Rahman et al, (2018); Rahmi & Tabroni, (2022); which argues that the practice of learning Tashih Recitations can improve Qur'an literacy skills.…”
Section: Introductionmentioning
confidence: 99%
“…As students who are prepared to teach Islamic religious subjects at school, then of course Islamic Religious Education students must have good competence in any content of religious subjects at school (Engkizar et al, 2021;Hasan, S., & Wahyuni, 2018;Khotimah et al, 2022). In other words, students who choose Islamic Religious Education must have good and correct competence in relation to religious studies themselves (Isnaini et al, 2022;Nurhidin, 2022).…”
Section: Introductionmentioning
confidence: 99%